2023
DOI: 10.1136/bmj-2023-076045
|View full text |Cite
|
Sign up to set email alerts
|

Association between recently raised anticholinergic burden and risk of acute cardiovascular events: nationwide case-case-time-control study

Wei-Ching Huang,
Avery Shuei-He Yang,
Daniel Hsiang-Te Tsai
et al.

Abstract: Objective To evaluate the association between recently raised anticholinergic burden and risk of acute cardiovascular events in older adults. Design Case-case-time-control study (ie, incorporating a case crossover design and a control crossover design consisting of future cases). Setting Taiwan’s National Health Insurance Research Database. Participants 317 446 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…ACB scores can give a useful guide to the risk of anticholinergic adverse events, although they do not consider drug dose, or offer an estimate of individual risk. A 2023 study13 found an association between recently raised anticholinergic burden and increased risk of acute cardiovascular events, with a greater increase in anticholinergic burden conferring higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…ACB scores can give a useful guide to the risk of anticholinergic adverse events, although they do not consider drug dose, or offer an estimate of individual risk. A 2023 study13 found an association between recently raised anticholinergic burden and increased risk of acute cardiovascular events, with a greater increase in anticholinergic burden conferring higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Taiwan’s NHIRD with 99.9% coverage of the population received 5 points (ie, very good) for population coverage and follow-up, but only 2 points (ie, poor) for clinical information. 27 …”
Section: Methodsmentioning
confidence: 99%
“…For example, Taiwan's NHIRD with 99.9% coverage of the population received 5 points (ie, very good) for population coverage and follow-up, but only 2 points (ie, poor) for clinical information. 27 The Common Data Model (CDM) concept means that all data partners convert their native databases to follow standardized data structures and terminologies, allowing the coordinating centre to generate a common analytic program that can be applied to all converted databases. 26 We assessed the essential data in the databases, such as enrollment period, patient characteristics, healthcare facility visit details, diagnosis details and drug details for their convertibility to a general common data model.…”
Section: Methodsmentioning
confidence: 99%
“…More recently Huang et al suggested in a nationwide population based study, an association between recently raised antimuscarinic burden and acute cardiovascular events in older adults 17 …”
Section: Antimuscarinic Drug Therapymentioning
confidence: 98%